Innovative Human Resource Development Strategies in Education Digital Transformation - Nurullayali Azzahro; Moh Ali (JIEM (Journal of Islamic Education Management), 2025)
The advancement of digital technology has brought significant changes to the education system, requiring institutions to fully integrate technological innovations into teaching processes and school management. This article aims to examine innovative strategies in the development of human resources (HR) in education during the digital transformation era through a scoping review method. Literature from various national and international journals (2021–2025) was analyzed to map practices, challenges, and strategies for developing adaptive and competitive educational HR. The findings indicate that innovative strategies include strengthening educators’ digital and pedagogical competencies, utilizing smart technologies such as e-learning, Learning Management Systems (LMS), webinars, as well as AI applications and VR/AR simulations, and fostering a collaborative and adaptive work culture through continuous training. This digital transformation enhances administrative efficiency, internal coordination, learning quality, and 21st-century competencies such as creativity, adaptability, critical thinking, and collaboration. However, implementing these strategies faces multidimensional challenges, including low digital literacy, limited infrastructure, resistance to change, disparities in technology-based pedagogical competencies, and data security risks. This study emphasizes that the development of educational HR in the era of disruption and Society 5.0 requires a systemic approach that combines individual competency enhancement, organizational culture strengthening, adaptive managerial policies, and optimal utilization of smart technologies. The findings provide insights for educational institutions to design innovative, sustainable HR strategies capable of addressing the complexities of 21st-century education.